(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract: In the present era of government began to implement the e-government program. The last few years the government has been utilizing technological advances in various activities, including the public service based on information technology gained recognition. Regional Personnel Agency (BKD) North Sulawesi Province. The agency is an agency that already use personnel information system to process data and information and decision-making for specific situations such as a promotion, a raise, a shift or mutation, and other relevant rules. Data and information is confidential and prudence. The method used in this research is qualitative research. Then, for the data used consist of primary data and secondary data. With the technique of collecting data through observation, interviews, and documentation. Data obtained from various sources and has analyzed, with several stages of data reduction, data presentation, and conclusion. Researchers infer from each corner of the data and information administration, employment applications, employee capability, equipment for the system, every administrative procedure. Researchers conclude that the management information system has been running well and answer the problem formulation management information system is a collection of elements that are interconnected with each other to form a single unit to integrate data, process and store and distribute information. At the Regional Employment Board of North Sulawesi these elements is the data and information of employees, employment applications, employee, equipment for the systems, and procedures for the administration. These elements are intertwined to be able to manage and deliver the results to the administration required. Keyword : System, Employee, SIMPEG, e-government.